Efficient Photoreduction of CO2 to CH4 on AgCl/Ag/g-C3N4 Ternary Composites - Hang, Dinh Thi Thuy; Bang, Nguyen Dinh; Binh, Nguyen Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1, 2026)
The AgCl/Ag/g-C 3 N 4 ternary composites were synthesized by simple methods. The characterizations (XRD, FTIR, TEM, UV-DRS, PL) indicated clearly the existence of Ag, AgCl, and g-C 3 N 4 phases and visible light absorption ability of composites. The photocatalytic activity was evaluated by photoreducing CO 2 to CH 4 . The obtained results showed that the composite 3AC-Ag-CN exhibited the highest activity with CH 4 production of 3.38.10 -2 mmol.g -1 .h -1 , which was ~7.5 times higher than that of g-C 3 N 4 . This activity enhancement was explained by their Z-scheme heterojunction structure.